Analisa Tebal Perkerasan Lentur Pada Ruas Jalan Siswondo Parman STA 0+000-1+000 Kabupaten Sumba Timur Provinsi Nusa Tenggara Timur - Andung Ngunjupraing, Irvibard Umbu ; Kristafy, Andi ; Suhudi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
The road is an important infrastructure for the community, especially in East Sumba district. But if the road is damaged, there will be a bad impact, such as congestion and the process of economic movement from one area to another becomes slow. Road damage is not only caused by the number of vehicles passing with a load that exceeds capacity but also from the drainage of environmental, climate and road planning factors that are not according to plan. One of the ways that experienced the problems above was Siswondo Parman East Sumba Regency East Nusa Tenggara Province. The purpose of the flexible pavement thickness analysis research on Siswondo Parman road in East Sumba Regency, East Nusa Tenggara Province is to calculate the thickness of flexible pavement and drainage dimensions. The pavement analysis method used is the SNI-03-1732-1989 Component Analysis method and the drainage planning method that is used is the Log Person type III method. The data used are primary data obtained directly, namely in the form of physical data on the location of the road and drainage research and the average daily traffic data. While secondary data from the Public Works service in the form of CBR data, rainfall data from the Meteorology, Climatology and Geophysics Agency, traffic growth data from the Transportation Agency. Data processing is adjusted to SNI-03-1732-1989 and Type III Log Person Method. From the results of the planning of the flexible pavement thickness, the thickness of the Laston surface layer is 7.5 cm, the thickness of the foundation layer on laston is 10 cm, and the bottom layer is the grade A 30 cm. Drainage dimensions obtained b = 0.45m and h = 0.22 m.